2009
DOI: 10.1038/cdd.2009.129
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii modulates Beclin 1 and Bcl-2, preventing host cell apoptosis to generate a persistent bacterial infection

Abstract: Coxiella burnetii is the etiological agent of the human disease, Q fever, and is an obligate intracellular bacterium that invades and multiplies in a vacuole with lysosomal characteristics. We have previously shown that Coxiella interacts with the autophagic pathway as a strategy for its survival and replication. In addition, recent studies have shown that Coxiella exerts anti-apoptotic activity to maintain the host cell viability, thus generating a persistent infection. In the present report, we have explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 50 publications
(87 reference statements)
1
66
0
2
Order By: Relevance
“…Beclin 1 mutant with defective Bcl-2 binding, suggesting that the interaction of Beclin 1 and Bcl-2 may modulate apoptosis. 33 These results support the idea, that under some circumstances, the BH3-only domain of Beclin 1 may competitively disrupt the binding of pro-apoptotic proteins (e.g., Bad) to Bcl-2 or Bcl-X L , thus avoiding the induction of apoptosis. Paradoxically, the results of Ciechomska et al showed that the binding of Beclin 1 to Bcl-2 does not modify the Bcl-2-mediated protection against apoptotic stimuli that initiates endoplasmic reticulum or mitochondria death signaling pathways.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Beclin 1 mutant with defective Bcl-2 binding, suggesting that the interaction of Beclin 1 and Bcl-2 may modulate apoptosis. 33 These results support the idea, that under some circumstances, the BH3-only domain of Beclin 1 may competitively disrupt the binding of pro-apoptotic proteins (e.g., Bad) to Bcl-2 or Bcl-X L , thus avoiding the induction of apoptosis. Paradoxically, the results of Ciechomska et al showed that the binding of Beclin 1 to Bcl-2 does not modify the Bcl-2-mediated protection against apoptotic stimuli that initiates endoplasmic reticulum or mitochondria death signaling pathways.…”
Section: Discussionsupporting
confidence: 76%
“…Because Beclin 1 plays a pivotal function in the regulation of cell death processes, 16,[31][32][33] we further investigated whether this protein plays a role in the viability of APL cells differentiated by ATRA. For this study, we downregulated Beclin 1 expression by using a specific siRNA that targets BECN1, and then evaluated autophagy and apoptosis during ATRA treatment of NB4 cells.…”
Section: Translational Brief Reportmentioning
confidence: 99%
“…Because multiple laboratories have recently employed avirulent NMII to investigate C. burnetii infection of host cells (1,30,38,50,54), it is important to ascertain the degree to which in vitro infection by NMII recapitulates infection by virulent NMI, particularly with respect to PV maturation in human mononuclear phagocytes. To this end, we directly compared the growth kinetics and PV maturation of NMI and NMII in human monocyte-derived macrophages (HMDMs) and phorbol 12-myristate 13-acetate (PMA)-differentiated THP-1 cells, which accurately mimic the properties of human primary macrophages (29).…”
mentioning
confidence: 99%
“…10 The mechanism for survival includes both altered expression of genes involved in apoptosis as well as increasing and blocking production of anti-and proapoptotic proteins respectively. 7,9,10 Increased apoptosis during disease states has been shown to be detrimental to the fetal viability, 6 but the significance of decreased apoptosis for NFS reproductive health and pup mortality is less clear. While placentas were collected from presumably successful live pup births, 4 nothing is known about the survival of the pup beyond placental detachment.…”
mentioning
confidence: 99%